Spatiotemporal dynamics of soil water-salt and its topographic gradient effects on Alpine area over the Northeastern Tibetan Plateau, China - Zhang, Xiaoning; Nian, Lili; Adingo, Samuel; Wang, Quanxi; Li, Xiaodan; Liu, Xuelu; Liu, Xingyu Y.; Yang, Yingbo; Hui, Caihong; Zhang, Miaomiao; Mao, Zixuan; Li, Quanxi; et al. (Frontiers in Environmental Science, 2022)
Soil water-salt variations at different spatiotemporal scales and its influencing factors are essential for regional vegetation restoration and management. However, the soil water-salt of alpine grasslands has not taken into account the effect of topography, especially in long time series. The paper investigated the spatiotemporal characteristics of water and salt in topsoil from 2000 to 2021 utilizing regression analysis and explored the heterogeneity of mean multi-annual and trends in different topographic factors (elevation, slope, aspect) using remote sensing. The results revealed that (i) The models applied to SWC (soil water content), EC (electric conductivity), and pH utilizing vegetation indices were suitable for estimating spatiotemporal variations of soil water-salt. (ii) Soil water-salt exhibited local aggregation characteristics with an upward trend in SWC as a whole, and a downward trend in EC and pH except for Maqu County. (iii) The mean annual SWC peaked at 3400–3800 m with increasing elevation and tended to downward with increasing slope. The aspect of mean annual of SWC was characterized by lower values in the southwest and south as well as higher values in the north whereas opposite outcomes for EC and pH. (iv) The rate of SWC and pH was more stable at elevations > 3600 m and slopes > 24°, and the absolute values of the rate revealed that the aspect had less impact on soil water-salt than elevation and slope. The results have significant implications for the implementation of ecological improvement in regions with complicated topography and can provide a reference for the formulation of future ecological policies.